Organizational and legal measures to prevent psychosocial risks caused by the war in Ukraine (Law and Safety, 2022)
The problem of the emergence of psychosocial risks among the population has become especially relevant in connection with the war in Ukraine. Therefore, there is a need for the development and implementation of effective measures to prevent such risks, to define guidelines for programme regulation in order to implement qualified psychological rehabilitation of the population.The basic principles of providing psychosocial and psychiatric care to persons with mental disorders are analyzed. The Concept of the development of mental health care in Ukraine for the period until 2030 and the need to develop other mental health and psychosocial support programmes are characterized, their target orientations, advantages and disadvantages are determined. The application of an individual approach is justified depending on the categories of citizens who need help, since the degree and nature of the traumas experienced can differ significantly. It is emphasized that mental health reforms should be non-intrusive and organic to reduce coercion and support mental health service users to make their own decisions about treatment. The special needs of people with mental disorders, including combatants, displaced persons, children, women, and the elderly, are identified. An integrated approach is emphasized, which would include the use of social, psychological, and medical measures at different levels (state, regional, and local) for the most effective intervention, providing the necessary support and accompaniment at various stages.The risks of the use of civilian firearms by the population of Ukraine in the context of the adoption by the Verkhovna Rada of Ukraine in the first reading of the draft Law of Ukraine “On the right to civilian firearms” are considered. It is emphasized the need to introduce a balanced permitting procedure in order to minimize risks against the background of the worsening situation in the field of mental health.Taking into account the experience of European countries, the possibility of functioning of interdisciplinary teams in the field of mental health, which are a basic element of the mental health care system in the community, has been considered. Based on the analysis of shortcomings and problems that arise in the process of receiving psychosocial services, practical recommendations have been developed to prevent psychosocial risks caused by the war in Ukraine.
Keywords: psychosocial risks; mental disorders; mental health care; combatants; displaced persons; psychological assistance programmes; psychosocial support.